The European wine export cycle - Leonida Correia; Sofia Gouveia; Patrícia Martins (Wine Economics and Policy, 2019)
Europe is the world's largest wine-producing and wine-exporting region. In recent decades, fostered by the liberalization of international trade, the European wine industry has witnessed an acceleration in its exports, but this increase has been far from steady. It has fluctuated considerably in the short term, where periods of rapid growth have alternated with slow or negative growth. In this context, it is of particular relevance to know the temporal dynamics of the fluctuations in wine exports and to discover whether there are cyclical co-movements with the European wine export cycle. This paper analyzes the cyclical synchronization of wine exports for the ten main European wine-producing countries with the aggregate European wine export cycle since the inception of the European Economic Community. The main objective is to investigate whether there has been a “European” wine export cycle over the last six decades. The cycles of wine exports are obtained using de-trending techniques, and Spearman's rank correlations and concordance indices are calculated to analyze the synchronization and interaction between cycles. The results for the exports, by value, revealed a strong degree of synchronization over the whole period for the majority of the countries, with a tendency to grow over time. Keywords: Wine, International trade, Synchronization, European union, JEL classification: E32, F14, F15